A commentary on Plutarch's Cato Minor - Geiger, J (1971)
The INTRODUCTION is concerned with the antecedents, the circumstances of writing and the structure of the biography. Its first chapter surveys the successive treatments of Cato's figure in the Roman literature: immediately after his suicide at Utica a great literary controversy around Cato came into being: cicero, and later Brutus, Fadius Gallus and Munatius Rufus wrote laudatory accounts while Caesar and A. Hirtius composed defamatory Anticatones. This theme was also central a few years later in Salluet's Catilinarian Conspiracy and was taken up by the aged Augustus in a rhetorical reply to Brutus. With the completion of the Roman revolution the theme of Cato lost its urgency and relevance and during the early Principate Cato's figure is reduced to a few stereotyped acts and situation discussed in the schools of Rhetoric. Yet under the reign of Claudius and Nero a revival in the interest in Cato takes place: Seneca regards him as the Stoic Saint Incarnate, his nephew Lucan makes him the chief hero of his Pharsalia, while Thrasea Paetus composes a full scale Life of Cato: for the senatorial opposition under Nero Cato's figure again has a political relevance. The reign of Domitian ensures the end of the literary preoccupation with Cato: hero worshippers found in Thrasea Paetus and Helvidius Priscus a more recent vintage of martyrs for the cause of libertas.